2016
DOI: 10.1242/dev.137075
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, survival and metabolism: the role of PI3K/AKT/mTOR signalling in pluripotency and cell fate determination

Abstract: Phosphatidylinositide 3 kinases (PI3Ks) and their downstream mediators AKT and mammalian target of rapamycin (mTOR) constitute the core components of the PI3K/AKT/mTOR signalling cascade, regulating cell proliferation, survival and metabolism. Although these functions are well-defined in the context of tumorigenesis, recent studies -in particular those using pluripotent stem cells -have highlighted the importance of this pathway to development and cellular differentiation. Here, we review the recent in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
567
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(629 citation statements)
references
References 112 publications
(147 reference statements)
22
567
1
6
Order By: Relevance
“…The PI3K-AKT signaling pathway comprehensively regulates cell survival, proliferation, metabolism, and stemness1011. Its acute activation in normal stem cells can lead to senescence or depletion of the stem cell pool2526, suggesting that it is tightly regulated in stem cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K-AKT signaling pathway comprehensively regulates cell survival, proliferation, metabolism, and stemness1011. Its acute activation in normal stem cells can lead to senescence or depletion of the stem cell pool2526, suggesting that it is tightly regulated in stem cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It can phosphorylate a number of key chromatin-modifying enzymes, such as the histone acetyltransferase p300, the DNA methyltransferase DNMT1, the H3K27 methyltransferase EZH2, and the histone ubiquitylating enzyme BMI1, altering the function of these enzymes9. Besides its well established roles in anti-apoptosis and cell survival, emerging evidence indicated that AKT is also a key player in stemness regulation and CSC biology, and thus a promising target for developing anticancer drugs against CSCs1011. OCT4, a master transcription factor controlling stem cell self-renewal and pluripotency, is considered as one of the most important mediators for cancer epigenetics8.…”
mentioning
confidence: 99%
“…Given that cellular metabolic processes are critical for the programming of stem cells (9)(10)(11), it raises the potential that maternal factors present in the OB intrauterine environment that affect energy regulation or differentiation may have significant impacts on the long-term programming and function of these cells, which exist in bone, muscle, and mature adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K-Akt-mTOR cues regulate various cellular functions, including nutrient uptake, cell proliferation, growth, autophagy, apoptosis, and migration (Hennessy et al 2005; Yu & Cui 2016). In the absence of extracellular stimulators, Akt is cytoplasmic and inactive (Alessi et al 1996).…”
Section: Introductionmentioning
confidence: 99%